Agropolis, or the city-region end. conceptual bases for a rural planning (2005)
This article explores the Region and the territory, under the influence of the theory and the history of the actual physical planning, from the modern dialectic between land and urban spaces. This relation, generates deep questions for urban regions. In those terms, the author explores the question about the city-region model, that in a preliminary, stage could be included in the “Agrópolis” concept